Effect of lean supply chain on competitive advantage: a systematic literature review - Zeyad Mustafa Hamed Khawka; Azmawani Abd Rahman; Shafie Bin Sidek; Siti Azfanizam Binti Ahmed; Rami Hikmat Fouad Al-Hadeethi; Tamadher Al-Dabbagh (Cogent Business & Management, 2024)
Undoubtedly, Lean Supply Chain Management (LSCM) has been widely identified as a powerful approach to improving supply chain performance and gaining competitive advantage (CA). Despite the challenges faced by numerous organizations in effectively implementing and sustaining lean practices. This research endeavor seizes the opportunity to conduct a comprehensive and methodical review of the existing literature to offer an in-depth examination of the relationship between LSCM and CA, focusing on the critical success factors (CSFs) for the lean supply chain that affect competitive advantage. The current study employed a systematic literature review (SLR) approach to identify studies on the relationship between LSCM and CA. A total of 529 published papers were selected from Web of Science (WoS), ScienceDirect, and Scopus databases. A comprehensive literature review was conducted, in which 55 relevant articles were analyzed from 2003 to 2023. The results revealed that the critical success factors (CSFs) for implementing LSCM can be broadly categorized into internal factors, external factors, and factors related to the implementation of LSCM. The most significant internal factors include customer focus, flexibility, cost reduction, time-to-market, and quality. External factors, such as collaboration with suppliers, customers, and other stakeholders, innovation, and technology, were also deemed critical. Effective LSCM practices such as lean principles, supply chain integration, information management, and logistics management are identified as significant contributors to success. The key results of this paper reveal that LSCM can be a practical approach for improving CA, as it addresses many of these critical success factors (CFSs). By adopting lean principles and integrating all aspects of the supply chain, firms can reduce waste, enhance efficiency, and improve responsiveness to customer demands. The study further discusses the current trends in LSCM and CA and provides implications for future research. However, the research has limitations, which include the restricted scope of the literature review and the lack of empirical research. In conclusion, this study provides valuable insights into the critical success factors (CSFs) for implementing LSCM and their effect on CA, which can benefit practitioners and researchers.In the current landscape of fierce business competition, staying ahead of competitors is imperative. Therefore, selecting the appropriate supply chain strategy has the potential to enhance the company's competitive advantage (CA). The adoption of lean supply chain management (LSCM) in recent years has generated conditions for substantial change in the way organizations manage their supply chains. However, research is still ongoing on how LSCM can be integrated into current supply chain models to improve CA and performance. LSCM is a powerful technique for improving supply chain performance and establishing a competitive edge, and the current study dives into this topic in depth. In recent times, there has been a notable surge in interest regarding the utilization of LSCM and its effect on CA. Yet, the existing knowledge about the advantages and obstacles of LSCM, which serve as driving forces and their connection to CA, is dispersed throughout various sources. This situation has spurred the creation of this paper, aiming to fill this gap through a systematic review of existing literature. Through a thorough examination of literature spanning from 2003 to 2023, this study aims to construct a holistic comprehension of how a lean supply chain influences CA by focusing on the crucial success factors (CSFs) for lean supply chain management that affect competitive advantage. Thus, this paper sheds light on achieving long-term success in a highly competitive market through lean supply chain implementation. Additionally, the connection between the efficient supply chain and CA offers greater motivation for professionals to utilize the implementation of LSCM in order to improve their organizations' CA. The present paper shows that internal aspects, including customer-centricity, adaptability, cost-cutting, speed-to-market, product quality, hand-by-hand with efficient LSCM procedures, and external elements such as teamwork and creativity, are crucial to enhancing CA.
Keywords: 650; supply chain management; lean principles; lean supply chain management; critical success factors; competitive advantage